2019
DOI: 10.1371/journal.ppat.1007798
|View full text |Cite
|
Sign up to set email alerts
|

ZAP’s stress granule localization is correlated with its antiviral activity and induced by virus replication

Abstract: Cellular antiviral programs encode molecules capable of targeting multiple steps in the virus lifecycle. Zinc-finger antiviral protein (ZAP) is a central and general regulator of antiviral activity that targets pathogen mRNA stability and translation. ZAP is diffusely cytoplasmic, but upon infection ZAP is targeted to particular cytoplasmic structures, termed stress granules (SGs). However, it remains unclear if ZAP’s antiviral activity correlates with SG localization, and what molecular cues are required to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…ZAP mutants revealed that recruitment to SGs correlates with ZAP antiviral activity. However, this study also indicated that ZAP interaction partners are important for antiviral function [265]. TRIM25, as an example, was shown to be an essential co-factor for the ability of ZAP to block SINV translation [359].…”
Section: Zinc-finger Antiviral Proteinmentioning
confidence: 70%
“…ZAP mutants revealed that recruitment to SGs correlates with ZAP antiviral activity. However, this study also indicated that ZAP interaction partners are important for antiviral function [265]. TRIM25, as an example, was shown to be an essential co-factor for the ability of ZAP to block SINV translation [359].…”
Section: Zinc-finger Antiviral Proteinmentioning
confidence: 70%
“…Rsad2-encoded viperin can impair budding of enveloped viruses [47][48][49] and alphavirus and flavivirus replication and assembly [50][51][52][53]. Zc3hav1 encodes zinc-finger antiviral protein (ZAP) or poly(ADP-ribose) polymerase-13 (PARP13), an RNA-binding protein that recruits RNA decay factors to degrade viral RNA and inhibit viral RNA translation [54][55][56][57][58]. However, the specific role for these ISGs in IFN-γ-mediated virus clearance from neurons will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, ZAP sensitivity of a panel of alphaviruses does not correlate with the CG dinucleotide content found in their genome or individual viral genes, suggesting that the CG dinucleotide motif is not the only determinant for ZAP recognition . The localization of ZAP to stress granules also appears to be functionally important for its antiviral activity against alphaviruses, as ZAP mutants that do not localize to SGs are unable to block SINV replication (Law et al 2019). In vivo, Zap knockout (Zc3hav1 −/− ) mice showed enhanced replication of SINV in 10-d-old mice as expected (Kozaki et al 2015).…”
Section: Ccch Znf Parpsmentioning
confidence: 95%